MODEL PEMBELAJARAN SKEMA PADA PELAJARAN BAHASA INDONESIA DAPAT MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS ULASAN SISWA KELAS VIII MADRASAH TSANAWIYAH NEGERI BINJAI - Faridah Hayati Lubis (Universitas Negeri Medan, 2021)
This study aims to find out that the implementation of the schema learning model in Indonesian lessons can improve reading comprehension skills for grade VIII Madrasah Tsanawiyah Negeri Binjai students in the Odd Semesters of the 2019/2020 Academic Year. The results showed that the schema learning model in Indonesian lessons could improve reading comprehension skills of the VIII grade students of Madrasah Tsanawiyah Negeri Binjai in the Odd Semesters of the 2019/2020 Academic Year. This can be seen from the results of the calculation in the first cycle between the value of the first daily test and the score of the second daily test, the Product Moment value is 0.823 with a t-test of 8.198. And the second cycle between the second block test scores and the third daily test scores obtained a Product Moment value of 0.903 with a t-test value of 11.902, while the results of the calculation showed that it was greater than the results in the table, of 0.478 and 2.725. Likewise, the average score for the first daily exam was 86.35, and the second daily exam was 87.53 in the first cycle, as well as the average score for the third daily exam was 88.53 and the fourth daily exam was 90.71 in the second cycle. there is an increase. while the minimum completeness criteria value (KKM is 84).Keywords: Schematic Learning Model, Reading Comprehension Skills Review Text